Power System Protection Vol. I: Principles and Components. (Institution of Engineering & Technology Books International, Inc. [distributor], 1995)
Annotation A set of four volumes compiled by leading authorities in the electricity supply industry and manufacturing companies to provide a comprehensive treatment of power system protection.
Keywords: Electric power transmission -- Great Britain -- Equipment and supplies.; Electric power systems -- Protection -- Great Britain.; Great Britain.; elektronické knihy; electronic books